Wasiat Wajibah bagi Ahli Waris Non-Muslim di Indonesia Perspektif Najmuddin At-Thufi - Aziz, Abdul; Maksum, Ghufron; Ali Asyari , Nadzif; Huda , Nurul (STAINI Press, 2023)
This article attempts to uncover, explore, and explain that the obligatory will for non-Muslim heirs is a contemporary issue that is not found in the texts of the Qur'an and Hadith. Departing from the dualism of the view that an ikhtiariyah will is a will given voluntarily and an obligatory will, namely a will that is obligatory in accordance with the law, the researcher wants to describe the Compulsory Will for Non-Muslim Heirs in Indonesia Through the Concept of Maslahah Mursalah Najmuddin At-Thufi. The method in this research is included in the category of library research in which the data and data sources of the researchers are obtained from various literatures (books, journals, internet, and other relevant data sources). This research proves that the obligatory will for non-Muslim heirs has a positive and equitable impact on family heirs. In addition to providing a sense of justice, obligatory wills to non-Muslim heirs through Supreme Court decisions have also filled the legal void in Indonesia